Lifetime prediction of bonded structural patch repairs for wind turbine pitch bearing strengthening. Issue 6 (26th April 2022) - Manterola, J.; Leciñana, I.; Zurbitu, J.; Zabala, H.; Urresti, I.; Olave, M.
ABSTRACT: There is a growing trend in the use of adhesively bonded patches to repair structures that are subjected to fatigue loads in an attempt to reduce the propagation of an existing crack. The fatigue lifetime prediction of the adhesive used in bonded patch repair is a state-of-the-art challenge, especially when in-service conditions must also be considered. Different approaches have been identified in the literature to analyse structural failure; the methods based on fracture mechanics seem more promising for adhesives because the presence of defects is also considered in the analysis. A considerable amount of work has been undertaken to analyse the delamination of layered structures using cohesive zone modelling (CZM). However, research analysing fatigue delamination in bonded thick-walled structures (> 30 mm) is lacking. The present work proposes a methodology to predict the lifetime of an adhesively bonded patch repair applied to a thick-walled structure, specifically looking at the bearing ring structural fatigue (RSF) life extension of a pitch bearing commonly used in wind turbines.